Zalora: Growing with e-commerce - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Asia’s fastest-growing online fashion retailer recalibrates its mobile strategy According to research by Forrester, one-fourth of global retail sales in 2022 will take place online, and it will be in Asia-Pacific. Of that, 80 percent of that will happen on mobile devices, reflecting a well-acknowledge trend of all things going mobile.